Impact Of Work-Related Stress On The Quality Of Life Among Nursing Officers In Selected Hospital - R. Velmurugan, R. Velmurugan; M. Abirami, M. Abirami (Journal of Neonatal Surgery, 2025)
Work-related stress has emerged as a critical challenge facing nursing officers, significantly impacting their quality of life (QoL). The dynamics of nursing environments are particularly punctuated by high-pressure situations, prolonged hours, emotional labor, and the necessity to make critical decisions, all of which collectively foster an atmosphere rife with stress-related issues. The study was approved by the ethics of the institution and it was a quantitative, cross-sectional study to assess the effect of the work-related stress on the quality of life of the nursing officers. The 150 nursing officers that were recruited were done through a convenience sampling technique from a hospital selected. Participants included nursing officers working in the hospital who were willing to participate and after optionally consenting. The nursing officers who were undergoing counseling for psychological therapy were excluded from the study. The study also found that moderate levels of work-related stress were experienced by most of the nursing officers and affected their quality of life. Moderate was the highest rating for physical health (46.7%), psychological health (43.3%), social health (40.0%), and environmental health (48.0%); poor QoL was perceived highest in social relationships (33.3%) and psychological health (30.0%). Major stressors were workload (43.3% moderate, 30.0% high), patient care (46.7% moderate), conflict with physicians (40% moderate) and lack of support (43.3% moderate). Those who worked shift had the lowest stress levels (40% low). The study concludes that the quality of life of nursing officers is highly influenced by moderate levels of work-related stress